PENGARUH MODEL PEMBELAJARAN INQUIRY TERHADAP KEMAMPUAN MENULIS KELAS IV SDN TENGGILIS MEJOYO I SURABAYA - Riris Rosiandani Arrochim; Danang Prastyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The inquiry learning model that is the background of this study is a series of instructional exercises that emphasize the application of critical thinking and analysis of problems submitted based on teacher guidance. This study aims to determine whether the inquiry model has an effect on the writing ability of class IV SDN Tenggilis Mejoyo I Surabaya. A quasi-experimental design with a nonequivalent posttest only control design was used in this study. 27 students from class IV A and 28 students from class IV became the research sample. The results of the normality and homogeneity tests showed that the variance was not homogeneous and the data were not normally distributed. Therefore, the Mann-Whitney test was used in this study. Based on the "test statistics" table in the Mann-Whitney test, it obtained 0.001 <0.05, which is a 2-tailed significance level, so H0 is rejected. Therefore, it can be said that the writing ability of the experimental and control groups is different. So the inquiry learning model has an effect on the writing ability of class IV SDN Tenggilis Mejoyo I Surabaya, the formulation of the problem can be solved.